Branding of Tourist Destinations - SHUTAIEVA, Elena; POBIRCHENKO, Viktoriya; KARLOVA, Anna; POLYUKHOVICH, Elena (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The objective necessity of an integrated approach to destination branding as a process of creating and managing a brand is substantiated. It is shown that the need to develop a strong and successful brand that enhances the image of a tourist destination is associated with fundamental changes in the nature of consumer behavior, due to the fact that for a potential tourist, choosing a vacation destination today is not only an indicator of lifestyle but also a certain status value. A cognitive analysis of the definitions of the concept of ''tourist destination brand" allowed formulating the authors' definition. According to the authors, a tourist destination brand is a combination of unique qualities, persistent universal values, reflecting the authenticity, unique and original consumer characteristics of this territory and community, which are widely known, gaining public recognition and enjoying stable tourist demand, contributing to the formation of preferences of this territory over others in a situation of choice. As a research method, modeling was used. Theoretically, it became possible to clarify the essence of the concept of "tourist destination brand" and systematically comprehend the technology of tourist branding by building the authors' model of the brand of tourist destinations. The authors of the article present the brand as the most important way to implement the competitive advantages of the territory, an instrument of competitiveness, differentiation, and uniqueness. Brands of tourist destinations are designed to emphasize the high quality of services not only in tourism and hospitality, restaurant business, but also in the use of public spaces.